Agrobacterium‐Mediated Transformation of Oilseed Rape (Brassica napus). Issue 4 (13th February 2018) - Bates, Ruth; Craze, Melanie; Wallington, Emma J.
Abstract: Oilseed rape ( Brassica napus ) is a commercially important member of the Brassicacea family. It is grown for its edible and industrial oils as well as for animal feed. Genetic transformation technology has been used to study gene function and produce oilseed rape with improved agronomic characteristics. This protocol describes a method for the Agrobacterium tumefaciens –mediated transformation of oilseed rape cotyledonary petioles. The method is reproducible and has been used to transform both spring and winter cultivars. Modifications have been made to the rooting stage, which have reduced the vitrification of shoots. This has not only increased the number of phenotypically normal shoots but has also resulted in an increase in transformation efficiency, concomitant with a dramatic reduction in the number of escapes regenerated. Transformation frequencies typically range from 5% to 10%, with an average of 12% using doubled haploid model varieties, but a maximum efficiency of 20% has been achieved. © 2017 by John Wiley & Sons, Inc.